Improving water use efficiency under worsening scarcity: Evidence from the middle Olifants sub-basin in South Africa - Teresa Walter; Julia Kloos; Daniel Tsegai (University of Bonn, Center for Development Research (ZEF), 2010)
With the political changes in South Africa in the early 1990s, the South African government introduced a reform process in the entire water sector with the goal of a more enhanced and equitable water management system. This paper analyzes existing water allocation situations and applies a nonlinear optimization model to investigate the optimal intra- and interregional allocations in the Middle Olifants sub-basin of South Africa. Results show higher benefit from interregional water allocation. Reducing water supply levels to conform to the sustainable water supply policy, it can be shown that although water supply is reduced by approximately 50%, total benefits from water are only reduced by 5% and 11% for inter- and intraregional allocation regimes respectively. These results indicate that alternative water allocation mechanisms can serve as instruments to offset for the effects of water scarcity.
Keywords: 330; Wasserpolitik; Reform; Wasserversorgung; Allokation; Gerechtigkeit; Südafrika